2016
DOI: 10.3390/su8090838
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Air Pollution Level in the City of Rome (Italy)

Abstract: Exposure to pollutants is usually higher in cities than in the countryside. Generally, in the urban areas pollution sources as traffic, power generator and domestic heating system are more intense and spatially distributed. The pollutants can be classified as a function of long-term toxicological effects due to an exposure and inhalation. In the present work, several kinds of pollutants concentration generated in Rome during 2015 have been analyzed applying different advanced post-processing technique. In part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 38 publications
(12 reference statements)
0
12
0
Order By: Relevance
“…The issue related to the assessment of air pollution/air quality has been widely engaged by empirical researchers for different geographical locations, and various approaches have been used to investigate this topic including land use regression modeling and mobile monitoring [29][30][31] , statistical analysis [32], multivariate analysis (including hierarchical agglomerate cluster analysis, principal component analysis, and multiple linear regression) [33,34], the proposed use of the air quality index [35], and the atmosphere evaluation and research integrated model [36].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The issue related to the assessment of air pollution/air quality has been widely engaged by empirical researchers for different geographical locations, and various approaches have been used to investigate this topic including land use regression modeling and mobile monitoring [29][30][31] , statistical analysis [32], multivariate analysis (including hierarchical agglomerate cluster analysis, principal component analysis, and multiple linear regression) [33,34], the proposed use of the air quality index [35], and the atmosphere evaluation and research integrated model [36].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Thus, to address this issue, two statistical extreme-value models for extreme events have been developed, namely the generalized extreme-value (GEV) and generalized Pareto distribution (GPD) models [10,11]. Both models have been found to be useful tools for providing good insights into the behaviors of extreme air pollution events [12][13][14][15][16][17][18][19][20][21]. For example, Al-Dhurafi et al [12] employed the GPD model to represent probability distributions in an unhealthy air pollution index for three highly polluted urban areas in Peninsular Malaysia.…”
Section: Introductionmentioning
confidence: 99%
“…Reyes et al [19] provided an estimation of the high ozone levels trend for seven of the meteorological stations located in the Metropolitan Area of Mexico city using the quantile function determined from a fitted GEV model. Battista et al [21] evaluated the behavior of the air pollution level in the city of Rome (Italy) using the GEV model. Overall, all of these studies found that the results obtained with extreme-value models provided valuable information to use as a basis of managing the risk of air pollution events.…”
Section: Introductionmentioning
confidence: 99%
“…Air pollution in recent years has become a serious environmental problem affecting people's health and lives [1][2][3]. Frequent exceeding the permissible limits of air pollution, especially in urban agglomerations [4][5][6][7], leads to trends limiting the emission of harmful factors in all branches of industry. Many years of efforts to limit emissions from internal combustion engines have led to a significant reduction in the production of unfavourable combustion products by this group of emitters.…”
Section: Introductionmentioning
confidence: 99%